The sceptical road : Aenesidemus' appropriation of Heraclitus - Polito, Roberto, 1966-. (Philosophia Antiqua, 2004)
The revival of Scepticism in the first century B.C. is due to Aenesidemus of Cnossus. Nonetheless, very little is known of him, and much of it seems to suggest that his thought tended more towards Dogmatism, and Heraclitean philosophy in particular. The puzzle has set the scene for a long-term debate, but, as yet, no agreed solution has been propounded. The present book provides a close examination of ancient evidence as well as of critical literature, and arrives at the conclusion that Aenesidemus merely intended to offer a Sceptical interpretation of Heraclitus, and that the ideas which are incorporated in it voice distinctive features of his Scepticism.